In vitro Test of Macrophage Phagocytic Activity of Extracts and Fractions of Red Dragon Fruit Peel [Hylocereus polyrhizus (F.A.C.Weber) Britton and Rose] - Wahdaningsih, Sri; Wahyuono, Subagus; Riyanto, Sugeng; Murwanti, Retno (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The peel of red dragon fruit [Hylocereus polyrhizus (F.A.C.Weber) Britton and Rose] can be used to treat various diseases and to improve immune system of body. This study was aimed to investigate the in vitro macrophage phagocytic activity of extracts and fractions of red dragon fruit peel (Hylocereus polyrhizus). The in vitro test was conducted based on the method of Leijh et al. The parameters of phagocytic activity were based on the macrophages capacity to phagocytose latex beads using the calculation of phagocytic capacity and phagocytic index. The test results indicated significant difference (p < 0.05). The petroleum benzene extract showed higher phagocytic activity of macrophages than methanol extract of the fruit peel, sediment, and media control (-). The LSD test showed that macrophage phagocytic activity using fractions (500 and 100 μg/ml) was significantly different from macrophage phagocytic activity using fractions (20 μg/ml), sediment (500, 100 and 20 μg/ml), extracts (500, 100 and 20 μg/ml), and media control. Dhaka Univ. J. Pharm. Sci. 17(2): 161-165, 2018 (December)